RNAi-mediated serotonin transporter suppression rapidly increases serotonergic neurotransmission and hippocampal neurogenesis - Ferrés-Coy, A (Nature Publishing Group, 2013)
Current antidepressants, which inhibit the serotonin transporter (SERT), display limited efficacy and slow onset of action. Here, we show that partial reduction of SERT expression by small interference RNA (SERT-siRNA) decreased immobility in the tail suspension test, displaying an antidepressant potential. Moreover, short-term SERT-siRNA treatment modified mouse brain variables considered to be key markers of antidepressant action: reduced expression and function of 5-HT(1A)-autoreceptors, elevated extracellular serotonin in forebrain and increased neurogenesis and expression of plasticity-related genes (BDNF, VEGF, Arc) in hippocampus. Remarkably, these effects occurred much earlier and were of greater magnitude than those evoked by long-term fluoxetine treatment. These findings highlight the critical role of SERT in serotonergic function and show that the reduction of SERT expression regulates serotonergic neurotransmission more potently than pharmacological blockade of SERT. The use of siRNA-targeting genes in serotonin neurons (SERT, 5-HT(1A)-autoreceptor) may be a novel therapeutic strategy to develop fast-acting antidepressants.